Implementasi Problem Based Learning dalam Pembelajaran Hak dan Kewajiban sebagai Upaya Memaknai Keterlibatan Siswa SD - Suaibah Aslamiyah Harahap; KMA Fauzi (Lembaga Yasin AlSys, 2025)
Although problem-based learning models have attracted considerable research attention, studies that specifically examine the application of Problem Based Learning (PBL) to strengthen understanding of rights and obligations in Pendidikan Pancasila instruction in primary schools remain limited. This study aims to describe how PBL can enhance students’ engagement, motivation, and conceptual understanding in real classroom contexts. It employs a descriptive qualitative approach with a field research design, involving all Grade IV students at SD IT Ar-Rakyu selected through total sampling. Data were collected through classroom observations, field notes, documentation, and analyses of students’ work, and subsequently analyzed through data reduction, data display, and conclusion drawing. The findings show that PBL fosters active participation, group collaboration, and deeper conceptual understanding, particularly when supported by multimodal media such as thematic videos, songs, posters, and contextual student worksheets (LKPD). These results contribute to the development of constructivist learning theory and extend understanding of PBL implementation in Pendidikan Pancasila within the context of Kurikulum Merdeka. The study concludes that student-centered, problem-oriented instruction plays an important role in enhancing motivation and character formation, and recommends that teachers integrate contextual problems, digital media, and structured role allocation in PBL. It also identifies opportunities for further research in broader contexts and for examining the long-term impact on students’ citizenship competencies.